Productivity of Cajuput Stands at Various Age Levels in Telawa Forest Management Unit, Central Java, Indonesia - Alvien Gusti Prasditio; Agustina, Ana; Rahmadwiati, Rissa; Pertiwi, Yus Andhini Bhekti; Wicaksono, Rezky Lasekti; Supriyadi (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Cajuput (Melaleuca cajuputi Powell) plants are essential oil-producing plants that have ecological and economic benefits. The ideal pruning life is one way to optimize the productivity of cajuput stands. This study aims to analyze the productivity of cajuput stands at various age levels in Telawa Forest Management Unit by considering shoots, stem diameter, shoot diameter, biomass, and land suitability analysis. Data was collected by making three temporary survey plots by simple random sampling at 5, 9, 13, 17, and 21-year-old stands. The results showed that cajuput stands experienced increased productivity, as seen in stem diameter, shoot diameter, and biomass. In addition, the higher the stand density, light intensity, and humidity positively affect the total biomass, with an increase in the life of the stand. Based on the study’s results, the best cajuput productivity occurred at 17-year-old stands, with an average biomass of 1,031.43 kg/ha and an allometric equation of 18.40 kg. The decrease in cajuput productivity occurred at 21-year-old stands, 40% compared to the 17-year-old stands, and the 21-year-old stands have the lowest land index value. Despite the decline in productivity, the main effects still need to be studied over a more extended period. Keywords: biomass, cajuput, optimal lifespan, productivity